BENEATH THE WAVES: OWNERSHIP AND CONTROL IN THE SUBMARINE CABLE INFRASTRUCTURE - Sick, Kristian (AoIR Selected Papers of Internet Research, 2026)
The Internet's growth in popularity over the last century has coincided with advances in artificial intelligence, streaming, and social media. This development has significant implications for internet infrastructure, which must accommodate increasing data usage from these technologies and growing user numbers. This study examines how the global submarine cable infrastructure is owned and controlled. It employs digital methods to collect quantitative data and uses visual network analysis to construct and analyse networks over these cables, their owners, and collaborations.Based on a political economy approach, the study identifies who owns and controls underwater cables and how this ownership has changed. The analysis concludes that the global network is owned by a diverse group of companies, dominated by older national telecommunications firms. In recent years, American "tech giants" have invested heavily in cable infrastructure, taking over the leading position.The study's findings contribute to the broader literature on infrastructure studies and offer insights into ownership, control, and power regarding this critical infrastructure. This knowledge can guide monitoring and regulation efforts, ensuring that this essential infrastructure benefits the public rather than private interests.